Dynamic Conditional Correlation Analysis of Stock Market Contagion: Evidence from the 2007-2010 Financial Crises - Mighri, Zouheir; Mansouri, Faysal (International Journal of Economics and Financial Issues, 2013)
This research examines the time-varying conditional correlations to the daily stock index returns. We use a dynamic conditional correlation (DCC) multivariate GARCH model in order to capture potential contagion effects between US and major developed and emerging stock markets during the 2007-2010 major financial crisis. Empirical results show substantial evidence of significant increase in conditional correlation or contagion as well as herding behavior during crisis periods. This result contrasts with the “no contagion” finding reached by Forbes and Rigobon (2002). Keywords: Dynamic correlation; DCC-GARCH; contagion; financial crisis; stock markets. JEL Classifications: C58